Multicointegração e políticas fiscais: uma avaliação de sustentabilidade para a América Latina - Bertussi, Luís Antônio Sleimann (Universidade do Vale do Rio do Sinos, 2008)
An economical event that the policymakers have been facing in the last decades, in Latin America, is the subject of the government's fiscal behavior and the consequent (un)sustainability of the public debt and your effects about the economy. The fact is that the government's debt increased exponentially at countless American Latin countries, becoming sometimes unsustainable in the short period, leading them to a defaults series. Therefore, the fiscal policy plays an important rule on the macroeconomic stabilization and on the economical cycles. Inside of this context, the present study has as general objective to evaluate the sustainability of fiscal policy of seven Latin America countries using the multicointegration methodology first apresented in Granger and Lee (1989, 1990) and, further, developed by Engsted, Gonzalo and Haldrup (1997) and Haldrup (1998) and Leachman et al (2005). The model presents a series of criterions to verify the existence of a multicointegration relationship among the receipts, sp
Keywords: restrição orçamentária intertemporal; sustentabilidade fiscal; multicointegração; fiscal sustainability; intertemporal budget constraint; multicointegration; Ciências Sociais Aplicadas